2021
DOI: 10.1111/cas.14863
|View full text |Cite
|
Sign up to set email alerts
|

Tumor‐associated macrophages promote the metastasis and growth of non‐small‐cell lung cancer cells through NF‐κB/PP2Ac‐positive feedback loop

Abstract: This is an open access article under the terms of the Creative Commons Attribution-NonCommercial-NoDerivs License, which permits use and distribution in any medium, provided the original work is properly cited, the use is non-commercial and no modifications or adaptations are made.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 57 publications
0
17
0
Order By: Relevance
“… 48 Many studies have reported that the invasion and metastasis of NSCLC are closely related to its microenvironment. 49 However, the link between the metastasis of NSCLC and macrophages and the underlying molecular mechanism have not yet been clarified.…”
Section: Discussionmentioning
confidence: 99%
“… 48 Many studies have reported that the invasion and metastasis of NSCLC are closely related to its microenvironment. 49 However, the link between the metastasis of NSCLC and macrophages and the underlying molecular mechanism have not yet been clarified.…”
Section: Discussionmentioning
confidence: 99%
“…2 Lung cancer cells can interact with immune cells and alter immune cell phenotypes that may contribute to the establishment of a tumor-supporting environment, which indicates resistance to cancer therapy. 3 As one of the main regulatory components in the tumor microenvironment (TME), tumor-associated macrophages (TAMs) are especially important in lung cancer, given their significant correlation with cancer growth, metastasis, patient prognosis, [4][5][6] and chemotherapy resistance. 7 Previous studies have suggested that TAMs can be functionally subtyped according to polarization status, namely M1-like and M2-like, and further demonstrated that M2-like TAMs play a tumorsupportive role in lung cancer.…”
Section: Introductionmentioning
confidence: 99%
“… 2 Lung cancer cells can interact with immune cells and alter immune cell phenotypes that may contribute to the establishment of a tumor‐supporting environment, which indicates resistance to cancer therapy. 3 As one of the main regulatory components in the tumor microenvironment (TME), tumor‐associated macrophages (TAMs) are especially important in lung cancer, given their significant correlation with cancer growth, metastasis, patient prognosis, 4 , 5 , 6 and chemotherapy resistance. 7 …”
Section: Introductionmentioning
confidence: 99%
“…They can be "domesticated" by tumour cells to polarize toward M2-like macrophages phenotype, therefore supporting tumour progression [49]. Many studies have reported that the invasion and metastasis of NSCLC is closely related to its microenvironment [50]. However, the link between the metastasis of NSCLC and M2 macrophages and the underlying molecular mechanism have not yet been clari ed.…”
Section: Discussionmentioning
confidence: 99%